2008
DOI: 10.1161/circresaha.107.163493
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin, an HMG-CoA Reductase Inhibitor, Exerts eNOS-Independent Protective Actions Against Angiotensin II–Induced Cardiovascular Remodeling and Renal Insufficiency

Abstract: Abstract-Angiotensin II (Ang II) plays a pivotal role in cardiovascular remodeling leading to hypertension, myocardial infarction, and stroke. Pitavastatin, an HMG-CoA reductase inihibitor, is known to have pleiotropic actions against the development of cardiovascular remodeling. The objectives of this study were to clarify the beneficial effects as well as the mechanism of action of pitavastatin against Ang II-induced organ damage. C57BL6/J mice at 10 weeks of age were infused with Ang II for 2 weeks and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 54 publications
(33 reference statements)
5
77
0
Order By: Relevance
“…Our previous study focused on endothelial expression of endoglin in the aorta where no atherosclerosis was detected, demonstrating reduced endoglin expression after statin treatment 45) . Moreover, pitavastatin treatment suppressed Angiotensin -induced enhancement of cardiac TGF-1 expression and Smad2/3 signaling and prevented fibrotic changes 46) . More recently, Shyu et al showed that atorvastatin decreased endoglin expression in cardiac fibroblasts, resulting in less collagen formation and less protein synthesis in cardiac fibroblasts, which indicates the potential role of endoglin in cardiac remodeling 47) .…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study focused on endothelial expression of endoglin in the aorta where no atherosclerosis was detected, demonstrating reduced endoglin expression after statin treatment 45) . Moreover, pitavastatin treatment suppressed Angiotensin -induced enhancement of cardiac TGF-1 expression and Smad2/3 signaling and prevented fibrotic changes 46) . More recently, Shyu et al showed that atorvastatin decreased endoglin expression in cardiac fibroblasts, resulting in less collagen formation and less protein synthesis in cardiac fibroblasts, which indicates the potential role of endoglin in cardiac remodeling 47) .…”
Section: Discussionmentioning
confidence: 97%
“…[17][18][19][20]22 However, less information is available about the effect of statins on the structural alterations of resistance arteries. Pitavastatin prevented the increase in media thickening of transversal sections from mouse coronary arteries after chronic Ang II infusion.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, several studies have shown that statins decrease blood pressure in variable degrees both in humans [11][12][13][14] and in experimental models, 15,16 although a lack of effect of statins on blood pressure levels has also been described. [17][18][19] Most of the benefits of statin therapy are attributable to the lowering of serum cholesterol levels. However, by inhibiting 3-hydroxy-3-methylglutaryl coenzyme A reductase, statins can also inhibit the synthesis of isoprenoids, which are important lipid attachments for intracellular signaling molecules, eg, Rho and Rac.…”
mentioning
confidence: 99%
“…Therefore, its effects in the liver and intestine appear to be limited and its distribution outside the intestines and/or portal system is minimal or non-existent. In addition to lipidlowering effects, statins exert numerous cardioprotective effects by increasing the bioavailability of vascular nitric oxide (NO) and by reducing oxidative stress and inflammatory cytokines [7][8][9] . However, it remains unknown whether ezetimibe manifests cardiorenal protective effects and improves metabolic disorders such as obesity, hypertension, insulin resistance, and renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%